2023
DOI: 10.1088/2040-8986/acd861
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent optical dispersion spectra for a single CeO2 thin-film layer in UV–vis and its reflection and transmission in the IR region

Abstract: CeO2 is a rare-earth refractory material with high refractive index, high thermal stability and infrared transparency; this knowledge can be utilized to develop practical thin films for high temperature thermophotovoltaics (TPVs) and thermal barrier coatings (TBCs). Here, we report ellipsometric measurements of a CeO2 thin film in the wavelength range 250 nm to 2500 nm from room temperature to 500°C. Because most previous spectroscopic studies of CeO2 evaluated its optical properties only at room temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The further differences between the simulated and measured reflectances using fabricated thicknesses may be attributed to other non‐ideal effects not captured in the simulation, such as interface quality, surface roughness and center‐to‐edge thickness variation. Previous studies [ 41,42 ] have also shown that there is also uncertainty in the optical constants of the fabricated layers.…”
Section: Resultsmentioning
confidence: 99%
“…The further differences between the simulated and measured reflectances using fabricated thicknesses may be attributed to other non‐ideal effects not captured in the simulation, such as interface quality, surface roughness and center‐to‐edge thickness variation. Previous studies [ 41,42 ] have also shown that there is also uncertainty in the optical constants of the fabricated layers.…”
Section: Resultsmentioning
confidence: 99%